Analisis Pembelajaran Pendidikan Jasmani dengan Platfrom Zoom Meeting pada Siswa kelas VIII SMP Negeri 2 Cilamaya Kulon - Regi Azhar Fakih; Ine Rahayu Purnamaningsih; Rolly Afrinaldi (Jurnal Ilmiah Wahana Pendidikan, 2022)
The problem of this research is how to analyze the learning of physical education with the Zoom Meeting platform for class VIII students of SMP Negeri 2 Cilamaya?. The purpose of the study was to determine the Analysis of Physical Education Learning with the Zoom Meeting Platform for VIII Grade Students of SMP Negeri 2 Cilamaya. Survey is the method used in this research and uses a quantitative descriptive approach. The sample used was 81 students using the sampling technique using the formulaSlovin's formula. Data collection in this study aims to obtain information about the Analysis of Physical Education Learning with the Zoom Meeting Platform for VIII grade students of SMP Negeri 2 Cilamaya. The data collection technique in this study was carried out with a questionnaire (questionnaire). From the results of this study, it is known that Physical Education Learning with the Zoom Meeting Platform for class VIII students of SMP Negeri 2 Cilamaya who stated in the "very good" category with a percentage of 38%, in the "good" category with a percentage of 48%, in the "good enough" category with a percentage of 48%. the percentage of 11%, in the "poor" category with a percentage of 2%, and in the "very poor" category with a percentage of 0%. So it can be concluded that Physical Education Learning with the Zoom Meeting Platform for Class VIII Students of SMP Negeri 2 Cilamaya is Good.